2015
DOI: 10.1080/19336950.2015.1051270
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of nociceptive ion channels and receptors via protein-protein interactions: implications for pain relief

Abstract: In the last 2 decades biomedical research has provided great insights into the molecular signatures underlying painful conditions. However, chronic pain still imposes substantial challenges to researchers, clinicians and patients alike. Under pathological conditions, pain therapeutics often lack efficacy and exhibit only minimal safety profiles, which can be largely attributed to the targeting of molecules with key physiological functions throughout the body. In light of these difficulties, the identification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 122 publications
0
12
0
Order By: Relevance
“…Rarely do proteins exert their functions alone. Rather, they are embedded in protein complexes and larger protein networks which enable the regulation and plasticity of cellular pathways (Alberts, 1998 ; Rouwette et al, 2015 ). Knowledge of such protein networks may therefore contribute to a mechanistic understanding of pathophysiological processes underlying SNI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rarely do proteins exert their functions alone. Rather, they are embedded in protein complexes and larger protein networks which enable the regulation and plasticity of cellular pathways (Alberts, 1998 ; Rouwette et al, 2015 ). Knowledge of such protein networks may therefore contribute to a mechanistic understanding of pathophysiological processes underlying SNI.…”
Section: Resultsmentioning
confidence: 99%
“…Several proteome studies have thus been conducted on chronic pain (Huang et al, 2008 ; Olausson et al, 2012 , 2015 ; Sui et al, 2014 ; Vacca et al, 2014 ). We are still lacking, however, an integrated systems-level view of protein network organization and dynamics (Alberts, 1998 ; Rouwette et al, 2015 ) in the somatosensory system. According to emerging network medicine efforts, the identification of cellular networks and in particular, distinct hubs of disease modules within these networks (Chapman et al, 2008 ; Barabási et al, 2011 ; Antunes-Martins et al, 2013 ; Borsook and Kalso, 2013 ; Chen et al, 2015 ), may hold great potential for diagnosis, patient stratification, and design of selective therapeutic interventions for chronic pain conditions (Gereau et al, 2014 ; Baron et al, 2017 ; Price and Gold, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In our studies, we not only observed an interaction of resolvins with MOR but also TRPA1 with MOR. In recent years, protein-protein connections have been analyzed in depth supporting the complexity of the pain pathway (Rouwette et al, 2015 ). Protein-protein interactions include receptors, kinases or adapter proteins.…”
Section: Discussionmentioning
confidence: 99%
“…However, the underlying mechanisms and active components have not been investigated. Since nociceptive action of BC was noted, it is reasonable to believe that BC may exert electrophysiological effect through altering characteristics of sarcolemmal ion channels to diminish I/R induced arrhythmias. Moreover, with its antioxidative and anti‐inflammatory effects, BC would also decrease myocytes loss during reoxygenation.…”
Section: Introductionmentioning
confidence: 99%